Agronomic Performance of IPB Maize Hybrids and Combining Ability of the Lines - Suwarno, Punjung Medaraji; Qadir, Abdul; Wijaya, Aldi Kamal; Suwarno, Willy Bayuardi (Department of Agronomy and Horticulture, IPB University, 2023)
Maize is a significant food crop consumed in numerous countries worldwide. Increasing the yield potential of maize can be achieved through the breeding of high-yielding hybrid varieties. The objectives of this study were to assess the performance of hybrid means and parent combining ability for grain yield and other agronomic traits using a line x tester mating design. The study took place at the Gunung Gede Experimental Station of IPB University, Bogor, from June to October 2022. The experiment was conducted using a randomized complete block design with a single genotype factor and three replications. Twenty-two hybrids were utilized as genetic materials, including 20 hybrid candidates and two check varieties. Six maize lines (H1, L26, Nei, P2B, and P42) were employed as line parents, while L15 and P10 were used as tester parents in the line x tester analysis. The neighbor-joining tree analysis indicated that the female parent has a significant influence on the agronomic and yield performance of the hybrids. Correlation analysis revealed that the yield is more strongly influenced by ear diameter rather than ear length, and it is more affected by the number of kernel rows than the number of kernels per row. Three selected hybrids with favorable traits were Nei x B1, L15 x L26, and L26 x P10. The parent L26 demonstrated relatively good general combining ability for yield and may be considered for future maize breeding program.